IMPLEMENTATION THE CODE OF CONDUCT FOR RESPONSIBLE FISHERIES IN PURSE SEINE OPERATIONS AND CATCH HANDLING - Sari, Iya Purnama; Tanjov, Yulia Estmirar; Affandi, Muhammad Yusuf (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2025)
The purse seine is one of the primary fishing gears used to land pelagic species at the Nusantara Fishing Port, Prigi. The adoption of environmentally responsible fishing practices is critical to minimizing bycatch, preventing habitat degradation, and preserving pelagic fish stocks. This study assessed the operational performance of small pelagic purse seines and catch-handling practices in relation to the CCRF. Fieldwork was conducted from February to May 2025 using purposive sampling, supported by observations and interviews with purse seine fishermen, including the stages of onboard and landing-site handling. A scoring system was applied to evaluate each indicator, and gap analysis was used to identify deficiencies in the handling system on KM. Sinar Mutiara. A total of 25 fishermen and 25 community respondents were surveyed, yielding an average score (X̅) of 28.78, indicating limited compliance with sustainable fisheries resource management principles. Variation in adherence to CCRF handling standards further reinforces this finding. While post-harvest handling at the auction site showed relatively better alignment with CCRF provisions, notable gaps remain in onboard and landing-site operations. These results underscore the need for targeted improvements to enhance compliance and support the transition toward more sustainable purse seine fisheries in Prigi.Keywords:       CCRF, handling of ctach, Prigi fishing port, purse seine